2013
DOI: 10.1530/boneabs.1.pp138
|View full text |Cite
|
Sign up to set email alerts
|

New chondrosarcoma cell lines and mouse models to study the link between chondrogenesis and chemoresistance

Abstract: Chondrosarcomas are cartilage-forming, poorly vascularized tumors. They represent the second malignant primary bone tumor of adults after osteosarcoma but in contrast they are resistant to chemotherapy and radiotherapy, surgical excision remaining the only therapeutic option. Few cell lines and animal models are available, and the mechanisms behind their chemoresistance remain largely unknown. Our goal was to establish new cell lines and animal cancer models from human chondrosarcoma biopsies to study their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A comprehensive analysis of DDC and COS showed that both had cartilage components. Monderer et al 25 found that cartilage components may have an inhibitory effect on chemotherapy. They constructed primary central chondrosarcoma cell lines from stage III tumors and DDC cell lines and designed a three-dimensional culture model to maintain their differentiation into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of DDC and COS showed that both had cartilage components. Monderer et al 25 found that cartilage components may have an inhibitory effect on chemotherapy. They constructed primary central chondrosarcoma cell lines from stage III tumors and DDC cell lines and designed a three-dimensional culture model to maintain their differentiation into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with the low proliferation rates of the tumor cells and the difficulty in reproducing an adequate environment for CS development (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that conventional in vitro assays based on monolayer cultures of tumor cells are not sufficient to reproduce the three‐dimensional (3D) structure of CS . To overcome this limitation, 3D chondrogenic culture models have been set up, in which CS cells cultured in 3D produce cartilaginous matrix, thus resembling the original tissue architecture. CS cells cultured in chondrogenic 3D pellets have been reported to be resistant to doxorubicin (DXR) and mafosfamide .…”
mentioning
confidence: 99%
“…To overcome this limitation, 3D chondrogenic culture models have been set up, in which CS cells cultured in 3D produce cartilaginous matrix, thus resembling the original tissue architecture. CS cells cultured in chondrogenic 3D pellets have been reported to be resistant to doxorubicin (DXR) and mafosfamide . Such 3D‐associated chemoresistance is very likely mediated by the tumor microenvironment that is recapitulated in the 3D structure, and that is typically characterized by hypoxic and acidic areas due to cancer cells tendency to glucose consumption with increased lactate production and a consequent high proton flow .…”
mentioning
confidence: 99%